Forecasting and The Relationship between Sukuk and Macroeconomy in Turkiye - Valencia Kirana Rosadhillah; Ülev, Salih (SMART Insight, 2024)
This study aims to forecast the outstanding of sovereign sukuk in the coming years and investigate the relationship between sukuk and macroeconomic variables, specifically inflation and exchange rate. This study applied a quantitative approach and took time series data of related variables in Turkiye from 2012 to 2021. The growth of Sukuk was predicted by using the Autoregressive Integrated Moving Average (ARIMA), while the Granger causality test was considered to investigate whether there is an interrelation among variables or not. The findings showed that the volume of sovereign sukuk has had positive progress in the following years. For the remaining analysis, both inflation and exchange rate affected significantly on sukuk outstanding. Meanwhile, the volume of sukuk did not affect both. In conclusion, there is no causal relationship between sukuk volume and macroeconomic variables. The findings of this study are limited since it only uses inflation and exchange rates as macroeconomic instruments. Moreover, it just observed the sukuk growth in Turkiye, which cannot be generalized to other countries. However, this paper will give a practical contribution to assist the government in making an efficient policy since sukuk is an alternative financing source to boost economic growth. Furthermore, this study can give a general view of the development of sukuk as a diversification instrument to stimulate the growth of Islamic finance industries in the future.